International Money Transfers; Paradoxes and the Balance-of-Payments - Steven Brakman; Charles van Marrewijk (CESifo GmbH, 2024)
The literature on international transfers has studied the possibility of transfer paradoxes; the donor gains and the recipient loses from a transfer. This can occur in a wide range of circumstances, including perfect competition and the absence of distortions. The literature, however, largely ignores the fact that most transfers are given in the form of money and not in real (consumption) terms. Money holdings reflect postponed consumption and requires that a time dimension enters the analysis. This aspect is ignored in the literature. We focus on money transfers in an otherwise standard set-up of a Walrasian perfect competition model. We determine whether transfer paradoxes are likely. We also study the welfare consequences of financial transfers for the donor and the recipient, and their impact on the Balance-of-Payments. We find that under normal circumstances transfer paradoxes do not occur, the donor's current account deteriorates and the recipient's current account improves.
Keywords: F32; F35; 330; money; transfers; international trade